THE ROLE OF EDUCATIONAL TECHNOLOGY IN DEVELOPING ACADEMIC WRITING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article provides a scientific analysis of the role of modern educational technologies in developing academic writing skills among students, the pedagogical effectiveness of digital tools, and the automation of text generation processes.
Keywords: educational technology, academic writing, digital literacy, artificial intelligence, corpus linguistics, formative assessment, higher education, writing methodology.